2013
DOI: 10.1007/s11010-013-1579-9
|View full text |Cite
|
Sign up to set email alerts
|

The novel estrogen receptor GPER regulates the migration and invasion of ovarian cancer cells

Abstract: G protein-coupled estrogen receptor (GPER) was identified as a new member of the estrogen receptor family in recent years. It has become apparent that GPER mediates the non-genomic signaling of 17β-estradiol (E2) in a variety of estrogen-related cancers. Our previous study has found that GPER was overexpressed in human epithelial ovarian cancer and was positively correlated with the expression of matrix metalloproteinase 9 (MMP-9), which suggested GPER might promote the metastasis of ovarian cancer. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 24 publications
6
42
2
Order By: Relevance
“…We demonstrated that KO/PyMT mice have fewer metastases compared with WT/PyMT mice, indicating that GPER plays a role in mammary tumor cell metastasis consistent with previous in vitro (16, 44, 50, 51) and clinical data (20). Several possible mechanisms have been observed for GPER-dependent tumor cell migration and invasion.…”
Section: Discussionsupporting
confidence: 90%
“…We demonstrated that KO/PyMT mice have fewer metastases compared with WT/PyMT mice, indicating that GPER plays a role in mammary tumor cell metastasis consistent with previous in vitro (16, 44, 50, 51) and clinical data (20). Several possible mechanisms have been observed for GPER-dependent tumor cell migration and invasion.…”
Section: Discussionsupporting
confidence: 90%
“…ER, estrogen receptor; GPER, G-protein coupled estrogen receptor; IGF-1R, insulin-like growth factor-1; PKCα, protein kinase C-α. estrogen receptor was shown to promote the proliferation and invasive behavior of several cancer cell lines, including breast (Girgert et al, 2012;Li et al, 2013;Pandey et al, 2009), endometrial (Du et al, 2012He et al, 2009;Ignatov et al, 2010;Vivacqua et al, 2006a), ovarian (Yan et al, 2013) and thyroid (Vivacqua et al, 2006b) cancer cells. Paradoxically, the G protein coupled estrogen receptor was also shown to mediate the inhibition of cancer cell proliferation, namely breast (Ariazi et al, 2010) and prostate cancer cells (Chan et al, 2010).…”
Section: The Knowledge Regarding the Mechanisms Of Action Of Antiestrmentioning
confidence: 99%
“…The effects of estradiol (E 2 ) on reproductive tract structure and function are well known. Recently, however, studies have indicated a role for E 2 in tumor initiation and progression through its promotion of the proliferative, migratory and invasive capabilities of cells (2)(3)(4)(5)(6). Many of the changes that occur in the endometrium during tumorigenesis are similar to those observed during implantation.…”
Section: Introductionmentioning
confidence: 99%